A Multilayer Ceramic Electrolyte for All‐Solid‐State Li Batteries. (16th December 2020) - Zhu, Jianxun; Li, XiaoLei; Wu, Changwei; Gao, Jian; Xu, Henghui; Li, Yutao; Guo, Xiangxin; Li, Hong; Zhou, Weidong
Abstract: Despite of the good stability with Li‐metal, Li6.75 La3 Zr1.75 Ta0.25 O12 (LLZTO) suffers from large interfacial resistance and severe Li‐metal penetration. Herein, a dual layer ceramic electrolyte of Ti‐doped LLZTO(Ti‐LLZTO)/LLZTO was developed, with the reducible Ti‐LLZTO layer contacting Li‐metal and the LLZTO layer contacting cathode. The identical crystal structures of Ti‐LLZTO and LLZTO enables a seamless contact and a barrierless Li + transport between them. The densities of Ti‐LLZTO pellets are higher than that of LLZTO. With an in situ reduction of Ti‐LLZTO by Li‐metal, the interfacial wettability was improved and a mixed ion‐electron conducting layer was created. Both features help to reduce defects/pores on interface and homogenize the interfacial ionic/electronic flux, facilitating the reduction of interfacial resistance and suppression of dendrites. With the help of Ti‐LLZTO layer, long‐term stable lithium plating/stripping was reached in an areal capacity of 3.0 mAh cm −2 . Abstract : A reducible Ti‐doped LLZTO was sintered on the surface of LLZTO, which not only exhibited higher density with less defects than undopted LLZTO, but also could in situ create a mixed ion‐electron conductor (MIEC) layer for homogenizing the interfacial ionic flux and electric field, benefiting to the interfacial wettability and suppression of dendrites.